Attitudes Towards Mathematics as Predictors of Preservice Teachers' Achievement in Senior Secondary School Chemistry - A.O.A. Awofala (Bulgarian Journal of Science and Education Policy, 2017)
A strong foundation in mathematics as a science of thinking may lead to an improved performance in chemistry. The study investigated attitudes towards mathematics as predictors of preservice teachers' achievement in senior secondary school chemistry among 325 Nigerian preservice chemistry teachers from two public universities in Lagos State, Nigeria using the quantitative research method within the blueprint of descriptive survey design of an expost facto type. Data collected were analysed using the descriptive statistics of mean, and standard deviation and inferential statistics of independent samples t-test, Pearson product moment correlation, analysis of variance and multiple regression analysis. Findings revealed that gender differences in attitudes towards mathematics and dimensions of attitudes towards mathematics among preservice chemistry teachers were at a zero-tolerance level while grade level of the preservice chemistry teachers was a factor in their attitudes towards mathematics. Grade level, gender and value in mathematics made statistically significant contributions to the variance in preservice teachers' achievement in senior secondary school chemistry. Based on the results of this study, it was recommended that chemistry teacher educators should emphasise the connec-tions between chemistry and mathematics for effective learning at the preservice teacher level.